Metabolic responses of Quercus ilex seedlings to wounding analysed with nuclear magnetic resonance profiling. (17th April 2013) - Sardans, J.; Gargallo‐Garriga, A.; Pérez‐Trujillo, M.; Parella, T.J.; Seco, R.; Filella, I.; Peñuelas, J.; Noctor, G.
Abstract Plants defend themselves against herbivory at several levels. One of these is the synthesis of inducible chemical defences. Using NMR metabolomic techniques, we studied the metabolic changes of plant leaves after a wounding treatment simulating herbivore attack in the Mediterranean sclerophyllous tree Quercus ilex. First, an increase in glucose content was observed in wounded plants. There was also an increase in the content of C‐rich secondary metabolites such as quinic acid and quercitol, both related to the shikimic acid pathway and linked to defence against biotic stress. There was also a shift in N‐storing amino acids, from leucine and isoleucine to asparagine and choline. The observed higher content of asparagine is related to the higher content of choline through serine that was proved to be the precursor of choline. Choline is a general anti‐herbivore and pathogen deterrent. The study shows the rapid metabolic response of Q. ilex in defending its leaves, based on a rapid increase in the production of quinic acid, quercitol and choline. The results also confirm the suitability of 1H NMR‐based metabolomic profiling studies to detect global metabolome shifts after wounding stress in tree leaves, and therefore its suitability in ecometabolomic studies.